Temporal Trends in the Diagnosis and Management of Childhood Obesity/Overweight in Primary Care - Nicole Nader; Vibha Singhal; Asma Javed; Amy Weaver; Seema Kumar (SAGE Publishing, 2014)
Objective: To determine the temporal trends in diagnosis and management of pediatric overweight/obesity by primary care providers at a single medical center. Patients: Children 2 to 18 years old undergoing a general medical examination during 3 calendar years (2003, 2006, and 2009). The number of visits for general medical examination were 6390 in 2003, 6646 in 2006, and 7408 in 2009. Methods: We performed a retrospective review of the electronic medical records for weight related diagnostic and/or management terms and laboratory screening in children with body mass index at or greater than the 85th percentile (n = 1630 in 2003, 1495 in 2006, and 1730 in 2009). Results: There was a significant increase in the diagnosis of obesity among obese children seen in 2009 (53.3%) compared with 2006 (36%, P < .001) and 2003 (24.3%, P < .001). Weight-related counseling was documented in a higher proportion of obese children in 2009 (49.4%) compared with 2006 (34.8%) and 2003 (26.6%). There was a significant increase in counseling regarding screen time in 2009 compared with 2006. A significant increase in screening for nonalcoholic fatty liver disease was also noted (30.5% in 2009 vs 21.9% in 2006, P = .018). Conclusions: There has been steady improvement in the rates of obesity diagnosis and obesity-related counseling by primary care providers. However, continued efforts to increase awareness of these issues are needed as nearly half of obese children remained undiagnosed and recommended laboratory screening for obesity-related comorbidities was performed in only a third of obese children.